Development of A Drama Text Writing Module Based On Character Education for Students Junior High School - Siregar, Ummi Aisyah (Jurnal Hata Poda, 2024)
This research aims to produce a drama text writing module based on character education for students at SMP Negeri 1 Batang Angkola. The research method used is the Research and Development research method which refers to the Borg and Gall model. The process of developing teaching materials for writing drama texts based on character education is carried out in three stages, namely the preliminary study stage, initial product development and product testing. The results of material expert validation on content suitability obtained an average of 88% in the very good category, the presentation feasibility aspect obtained an average of 84.33% in the very good category and the language assessment obtained an average of 82.5% in the very good category. for graphic assessment by design experts, an average of 80.08% was obtained in the good category. Individual trials obtained an average percentage of 79.77 in the "good" category. Small group trials obtained an average percentage of 85.96 in the "very good" category. Limited field trials obtained an average percentage of 91.87 in the "very good" category. Based on these data, teaching materials that are suitable for teachers and students to use in learning are obtained. Teaching materials for writing drama texts based on character education were declared effective in generating student activity and learning outcomes. This is proven by tests on student learning outcomes in writing drama texts. At the pretest the average was 69 and at the posttest the average was 80. The difference between the pretest and the posttest was 11%, which indicated that learning using teaching materials for writing drama texts based on character education was better than before.